UPAYA PENINGKATAN APRESIASI MAHASISWA DALAM PROSES PEMBELAJARAN AGAMA ISLAM DI UNIVERSITAS MADURA PAMEKASAN JAWA TIMUR - Marsum Marsum; Syaiful Anam (Fakultas Agama Islam Universitas Islam Madura, 2023)
Lecturers have an important role in fostering student enthusiasm for learning through various learning motivations based on individual experience and concern. In addition to lecturers, parents also play an active role at home providing motivation and encouragement for students' skills at the university in carrying out the learning process. Such as giving appreciation or appreciation by using words with very good, great and amazing words. Strengthening or motivation that is done verbally contains assessments and awards that can lead to interactions and personal experiences for students. The research method used by researchers is descriptive qualitative. The informants in this study were some of the students the researchers met in the field, who the researchers then combined with other informants. Data collection methods are interviews, field observations and documentation data analysis. The results of the research that the researchers managed to find included students at the University of Madura Pamekasan who were less motivated in the learning process of Islam, because it was considered normal, so that the level of student appreciation for learning did not allow it to be maximized. The implication of this research is that education practitioners from the elementary, secondary and tertiary education unit levels have a complete picture of the problems of Islamic religious education which will then be used as material for improving the implementation of education in the future